Transitions Into and Out of Work: Stay-at-Home Fathers' Thoughts and Feelings: A Brief Report. Issue 3 (October 2021) - Jones, Catherine; Wells, Jasmine; Imrie, Susan; Golombok, Susan
This qualitative study explored how stay-at-home fathers (SAHFs) think and feel about transitioning back into paid employment. Findings from a thematic analysis on interviews with 21 SAHFs in the United Kingdom revealed that many of the SAHFs expected to return to work. However, most of the fathers suggested that this would be part-time, or self-employment, which would allow them to remain highly involved in caregiving, representing their commitment to moving away from the traditional gender roles that are largely evident in parenting. Some fathers expressed a desire to return to the paid workforce whilst others showed apprehension, indicating tensions over negotiating work and care. These findings have practical implications for fathers who are highly involved in caregiving.